The psychological health of Nursing professionals during direct coping with COVID-19 in Brazil (Research, Society and Development, 2020)
This study aimed to report the experience of a group of academic and nursing technicians who worked in health care, directly and indirectly, of patients with COVID-19 during the pandemic of the year 2020. It is an experience report, exploratory and descriptive, of five academic and nursing technicians, in private and public hospitals and in a private clinic, both in the state of Rio de Janeiro, from March to June 2020. The professionals' experience during the pandemic time caused several conflicts to them, strongly affecting their mental and emotional health. Feelings such as fear, anxiety and worry were frequently reported, especially those who acted in environments where it was not possible to know whether the patient had coronavirus or not since, up to a certain point, it was not always possible to use personal protective equipment necessary to all professionals. Although the negative impact caused by the pandemic of the new coronavirus was great, the professionals also reported that, after working during this period, they felt more confident and safer in developing nursing, paying attention to the need to follow basic hygiene and biosafety standards and also the need for greater appreciation of nursing professionals by institutions in general, providing at least equipment and materials for the proper development of care.